Investigation on the Flow Characteristics of Complex Flow Channel System of Mixed-flow Pump with Impulse Operation. Issue 1 (1st June 2022) - Sun, Mingkang; Xu, Jin; Huang, Chuibing; Zhang, Xiaoping; Huang, Zhenwei
Abstract: How to construct a turbulence model applicable to the flow characteristics of complex flow channel system in mixed-flow pump with impulse operation is of great importance, both for the numerical simulation accuracy of complex flow channels and the subsequent study of transient flow mechanism. In this paper, based on the closure parameters Cε2 and Cμ, a new turbulence model is proposed for the study on flow characteristics of complex flow channel system in mixed-flow pump with impulse operation. Experimental measurement and numerical calculation reveal that the closure parameters Cε2 and Cμ in the turbulence model have an important impact on the calculation accuracy compared with other closure parameters. The results indicate that appropriate reduction of the two parameters can effectively promote the calculation precision. Compared with the traditional turbulence model, the maximum error in the numerical calculation of the new turbulence model is reduced by 30%. The research in this paper lays the theoretical foundation for the transient flow mechanism of complex flow channel system in mixed-flow pump with impulse operation.